UPAYA GERAKAN ME TOO MENGURANGI KEKERASAN SEKSUAL PADA PEREMPUAN DI INDIA TAHUN 2018 - Rakhmadhani, Haldhianty Fitri; Sushanti, Sukma; Nugraha, A.A Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT The aim of this research is explaining the effort of Me Too movement in reducing the number of sexual harassment in India in 2018. Me Too movement comes from USA and campaigned India in 2012. This movement is intended to reduce the number of sexual harassments in India. Various attempts were done by Me Too movement in order to reduce the number of sexual harassments in India, one of them is through social media campaign. This research is using quasi-qualitative method with social movement and radical feminism as its conceptual framework. Using the radical feminism in its efforts, Me Too movement becomes a platform for Indian women in facing sexual harassment and changing the mindset of the society about the sexual harassment. This movement is urging Indian women to speak in public about sexual harassment that they experienced. Keywords: India, Sexual Harrasment, Social Movement, Me Too Movement, Radical Feminism.